A Snapshot of Current Updates and Future Prospects of 3D Printing in Medical and Pharmaceutical Science - Agrawal, Rutvi; Garg, Akash; Deshmukh, Rohitas (Current Pharmaceutical Design, 2023)
3D printing in other fields, such as aviation, is quite old, but in the pharmaceutical area, it is an emerging technique. 3D printing is used to formulate various drug delivery systems and dosage forms with complex geometry. It allows large and fast production of products according to the need of the patient. Today, it is the widely used manufacturing technique in the healthcare field for the engineering of tissues and tissue models, production of medicines and medical devices, organ and tissue bioprinting, implant manufacturing, and production of polypills, vaginal rings, orodispersible films, etc. It allows the production of various dosage forms with complex release profiles containing multiple active ingredients. It is used for manufacturing medicines according to the need of individual patients focusing on the concept of personalized medicines. The idea of customized medicines allows change of dosage and design of the product as per individual and with decreased side effects. This review details various techniques of 3D printing used, such as stereolithography, fused deposition modeling, inkjet printing, etc., and applications and dosage forms developed with the latest patents. The significant challenges in the emergence of the 3D printing technique are the involvement of complex combinations to achieve desired properties, and also, the bioprinter involved provides slow and less resolution. The materials prepared by this technique are both biocompatible and printable, due to which additive manufacturing is increasing in the field of medicine.
Keywords: extrusion-based printing